A highly sensitive formaldehyde gas-sensitive material and its preparation method and application
The preparation of Au and Sm-doped modified lanthanum ferrite formaldehyde gas-sensitive material was solved by electrospinning, which solved the problem of inaccurate detection of low-concentration formaldehyde gases in the prior art, and achieved high sensitivity and selective formaldehyde gas detection.
Patent Information
- Application Number
- CN202410396661.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-04-03
AI Technical Summary
Existing formaldehyde gas sensors cannot effectively detect low-concentration formaldehyde gas, and have low sensitivity to formaldehyde, which cannot meet the demand for low-concentration formaldehyde gas detection.
The Xwt% Au-La1-ySm yFeO3 formaldehyde gas-sensitive material was prepared by electrospinning method, and the lanthanum ferrite material was doped and modified by Au and Sm to prepare a gas-sensitive material with a hollow tubular nanostructure.
High sensitivity detection of formaldehyde gas is achieved, with high selectivity and short response-response recovery time, which can effectively reduce the lower limit of formaldehyde gas detection concentration.
Smart Images

Figure CN118294503B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of formaldehyde gas detection, and in particular to a highly sensitive formaldehyde gas-sensitive material and a preparation method and application thereof. Background Art
[0002] Formaldehyde is a colorless, pungent, toxic gas that often appears in interior decoration materials. Long-term exposure to formaldehyde can cause symptoms such as dizziness, headaches, leukemia, and even death. For low-concentration formaldehyde gas, long-term exposure can cause fatigue, sensory impairment, reduced immunity, drowsiness, memory loss, neurasthenia, depression, and even respiratory dysfunction and liver toxicity, manifested as liver cell damage, abnormal liver radiation, etc. Therefore, the detection of formaldehyde gas, especially low-concentration formaldehyde gas, is extremely important.
[0003] At present, the sensors used to detect target gases are mainly divided into electrochemical, optical fiber and semiconductor gas sensors. Among them, semiconductor gas sensors have the advantages of high sensitivity, simple preparation and low cost, and have become the mainstream gas sensors in the commercial field.
[0004] In the prior art, the journal La 1-x Sm x Preparation of FeO3 Nanopowders and Study on Gas Sensing Properties" (Zhang Ru et al., Electronic Components and Materials, Vol. 30, No. 1, January 2011) disclosed that LaFeO3 was doped with Sm at the A position and LaFeO3 was prepared by citric acid sol-gel method. 1-x Sm x FeO3 nanopowder. But the La 1-x Sm x The gas sensor made of FeO3 nanopowder has high sensitivity and low operating temperature to ethanol gas, but low sensitivity to formaldehyde and cannot detect low concentration formaldehyde gas.
[0005] At present, mainstream formaldehyde gas sensors can generally only detect formaldehyde gas above 10ppm. They are not very accurate for low-concentration formaldehyde gas and are prone to false alarms. However, the detection of low-concentration formaldehyde gas is extremely important. Therefore, the development of semiconductor gas sensors with high sensitivity and selectivity for low-concentration formaldehyde gas has very important social significance and economic value. Summary of the invention
[0006] Based on the above-mentioned deficiencies in the prior art, the purpose of the present invention is to propose a highly sensitive formaldehyde gas-sensitive material and a preparation method and application thereof, and to use the gas-sensitive material for a low-concentration formaldehyde gas sensor, which can effectively reduce the lower limit of detection concentration of formaldehyde gas, and at the same time have high sensitivity and selectivity, simple preparation process, low cost, and are suitable for large-scale commercial use.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect of the present invention, a formaldehyde gas-sensitive material is provided, wherein the formaldehyde gas-sensitive material is Xwt% Au-La y Sm 1-y FeO3, Xwt% is the doping amount of Au in the formaldehyde gas sensitive material, 0.5%≤Xwt%≤3%, 0<y≤0.3.
[0009] Preferably, the formaldehyde gas-sensitive material has a hollow tubular nanostructure.
[0010] Preferably, the formaldehyde gas-sensitive material has an average particle size of 70-90 nm, an average pore size of 5-18 nm, and a specific surface area of 18.0-18.5 m 2 / g.
[0011] The second aspect of the present invention provides a method for preparing a formaldehyde gas-sensitive material, comprising the following steps:
[0012] (1) lanthanum nitrate, iron nitrate, samarium oxide, N,N-dimethylformamide and polyvinyl pyrrolidone are mixed and dissolved in dilute nitric acid to obtain a mixed solution, and chloroauric acid is added to the mixed solution, and stirred to obtain a precursor solution;
[0013] (2) The precursor solution is prepared into a fiber intermediate by an electrostatic spinning method, and the fiber intermediate is calcined and ground to obtain a formaldehyde gas-sensitive material.
[0014] Preferably, in step (1), the added amount ratio of the lanthanum nitrate, ferric nitrate, samarium oxide, N,N-dimethylformamide, polyvinyl pyrrolidone, chloroauric acid and dilute nitric acid is (0.5-3) mol: (0.5-3) mol: (0.01-0.2) mol: (30-60) mL: (20-50) g: (1-20) g: (100-200) mL.
[0015] Preferably, in step (1), the mass fraction of nitric acid is 8.5%.
[0016] Preferably, in step (1), the stirring time is 3-6 hours.
[0017] Preferably, in step (2), during the electrospinning process, the electrostatic voltage range is 10Kv-20kV, the distance between the needle of the syringe used for electrospinning and the collector is 10cm-20cm, and the injection rate is 0.5mL / h-0.8mL / h.
[0018] Further preferably, the collector is aluminum foil.
[0019] Preferably, in step (2), the calcination temperature is 600-800° C. and the calcination time is 2-5 h.
[0020] Preferably, in step (2), the grinding time is 3-6 hours.
[0021] The third aspect of the present invention provides the use of formaldehyde gas-sensitive materials in detecting formaldehyde and preparing formaldehyde gas-sensitive sensors.
[0022] Preferably, the concentration of formaldehyde is 0.1-5 ppm.
[0023] A fourth aspect of the present invention provides a method for preparing a formaldehyde gas sensor, comprising the following steps:
[0024] The formaldehyde gas-sensitive material, deionized water and pine alcohol are mixed to obtain slurry; the slurry is spin-coated on the surface of an aluminum oxide ceramic tube and aged to obtain a formaldehyde gas-sensitive sensor.
[0025] Preferably, the added amount ratio of the formaldehyde gas-sensitive material, deionized water and pinene alcohol is (1-3) g: (3-9) mL: (1-3) mL.
[0026] Preferably, the spin coating speed is 600 rpm and the coating thickness is 3-8 μm.
[0027] Preferably, the aging temperature is 180-240° C., and the aging time is 16-24 h.
[0028] Beneficial effects of the present invention:
[0029] Xwt% Au-La prepared by electrospinning y Sm 1-y FeO3 formaldehyde gas-sensitive material has a hollow tubular nanostructure, a large specific surface area, and many pores, which are conducive to the transmission and diffusion of gas. The modification of the surface of the material by the precious metal Au will change the potential barrier on the surface of the material on the one hand, which is manifested as a change in the initial resistance of the material; on the other hand, it will increase the activity of gas molecules, enhance the degree of redox reaction and increase the reaction rate, which is manifested as the gas-sensitive material has higher responsiveness, selectivity and shorter response-recovery time to formaldehyde gas. The rare earth element Sm doping can change the lattice shape inside the material, causing defects, thereby affecting the electrochemical properties of the material.
[0030] The present invention performs Au and Sm doping modification on lanthanum ferrite material to obtain a gas-sensitive material that can be used to detect 0.1-5ppm formaldehyde gas, and the doping modification by combining Au and Sm has a synergistic effect in improving the sensitivity and selectivity of low-concentration formaldehyde detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 1 and 2. These are XRD diagrams of the formaldehyde gas-sensitive materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1.
[0032] Figure 2 This is the SEM image of the formaldehyde gas-sensitive material prepared in Example 1.
[0033] Figure 3 It is the EDS graph of the formaldehyde gas-sensitive materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1.
[0034] Figure 4 This is a graph showing the relationship between the gas-sensing performance of the formaldehyde gas-sensitive materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1 to 1 ppm formaldehyde and temperature.
[0035] Figure 5 It is a relationship diagram between the gas-sensing properties of the formaldehyde gas-sensitive materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1 and the formaldehyde gas concentration.
[0036] Figure 6 It is a schematic diagram of the response of the formaldehyde gas-sensitive materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1 to 1 ppm of various gases.
[0037] Figure 7 It is a dynamic schematic diagram showing the response of the formaldehyde gas-sensitive materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1 to different concentrations of formaldehyde gas changing over time under the same working temperature and humidity environment.
[0038] Figure 8 This is a relationship diagram between the gas-sensitive performance of the formaldehyde gas-sensitive materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1 to 1 ppm formaldehyde and the relative humidity of the environment. DETAILED DESCRIPTION
[0039] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0040] As mentioned in the background technology, in the prior art, formaldehyde gas sensors can only detect formaldehyde gas > 10ppm, but the national regulations stipulate that the indoor formaldehyde content shall not exceed 62ppb. Therefore, it is necessary to have a formaldehyde gas-sensitive material for semiconductor gas sensors to achieve high sensitivity and high selectivity detection of low-concentration formaldehyde gas.
[0041] Based on this, the present invention provides a highly sensitive formaldehyde gas-sensitive material and its preparation method and application. The formaldehyde gas-sensitive material is prepared by doping and modifying lanthanum ferrite material with Au and Sm at the same time, and the doping amounts of Au and Sm are controlled so that the formaldehyde gas-sensitive material has a hollow tubular structure, which can realize high-sensitivity detection of low-concentration formaldehyde gas.
[0042] Specifically, the average particle size of the obtained formaldehyde gas-sensitive material is 60-100nm, the average pore size is 5-18nm, and the specific surface area is 18.0-18.5m 2 / g. When the grain size is close to or smaller than the Debye length of the sensor material, the grain size will significantly affect the gas-sensitive performance of the sensor material, while rare earth doping will greatly reduce the grain size of the sample, which is beneficial to the gas-sensitive response. The smaller the particle size of the material, the larger the relative specific surface area, which can provide more adsorption sites for the target gas, and the surface of the material can adsorb more target gas to produce a corresponding more intense redox reaction; within the mesoporous range, the more pore sizes, the more transport channels provided to the target gas, which can also intensify the corresponding redox reaction of the target gas on the surface of the material, making the material show better gas-sensitive performance.
[0043] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0044] Example 1: Preparation of formaldehyde gas sensor
[0045] (1) Lanthanum nitrate, iron nitrate, samarium oxide, N,N-dimethylformamide and polyvinyl pyrrolidone are mixed and dissolved in dilute nitric acid to obtain a mixed solution, and chloroauric acid is added to the mixed solution and stirred for 6 hours to obtain a precursor solution;
[0046] The added amounts of the lanthanum nitrate, ferric nitrate, samarium oxide, N,N-dimethylformamide, polyvinyl pyrrolidone, chloroauric acid and dilute nitric acid are 292.41 g: 241.85 g: 17.44 g: 30 mL: 30 g: 2.43 g: 100 mL.
[0047] (2) preparing a fiber intermediate from the precursor solution by electrospinning, wherein the electrostatic voltage range is 20 kV, and the distance between the needle of the syringe used for electrospinning and the collector aluminum foil is 14 cm;
[0048] The fiber intermediate was calcined at 750°C for 5 hours to ensure that the hydrocarbons in the fiber intermediate were completely burned out. After cooling to room temperature, the fiber intermediate was evenly ground for 6 hours to obtain a 1wt% formaldehyde gas-sensitive material.
[0049] Au-La 0.9 Sm 0.1 FeO3, the particle size of the formaldehyde gas-sensitive material is 60-100nm;
[0050] (3) The formaldehyde gas-sensitive material, deionized water and pine oil were mixed in an addition ratio of 1 g:3 mL:1 mL to obtain a slurry, which was spin-coated on the surface of an aluminum oxide ceramic tube at a rotation speed of 600 rpm to a coating thickness of 3 μm. The tube was aged in air at 210° C. for 20 h to obtain a formaldehyde gas-sensitive sensor.
[0051] Example 2: Preparation of formaldehyde gas sensor
[0052] (1) dissolving lanthanum nitrate, iron nitrate, samarium oxide, N,N-dimethylformamide and polyvinyl pyrrolidone in dilute nitric acid to obtain a mixed solution, then adding chloroauric acid to the mixed solution and stirring for 3 hours to obtain a precursor solution;
[0053] The added amounts of the lanthanum nitrate, ferric nitrate, samarium oxide, N,N-dimethylformamide, polyvinyl pyrrolidone, chloroauric acid and dilute nitric acid are 292.41 g: 241.85 g: 17.44 g: 40 mL: 40 g: 2.43 g: 150 mL.
[0054] (2) preparing a fiber intermediate from the precursor solution by electrospinning, wherein the electrostatic voltage range is 10 kV, and the distance between the needle of the syringe used for electrospinning and the collector aluminum foil is 10 cm;
[0055] The fiber intermediate is calcined at 600° C. for 4 hours to ensure that hydrocarbons in the fiber intermediate are completely burned out. After cooling to room temperature, the fiber intermediate is evenly ground for 3 hours to obtain a formaldehyde gas-sensitive material having a particle size of 60-100 nm.
[0056] (3) The formaldehyde gas-sensitive material, deionized water and pine oil were mixed in an amount ratio of 3 g:9 mL:3 mL to obtain a slurry, and the slurry was spin-coated on the surface of an aluminum oxide ceramic tube at a rotation speed of 600 rpm to make a coating thickness of 8 μm. The tube was aged in air at 180° C. for 24 h to obtain a formaldehyde gas-sensitive sensor.
[0057] Example 3: Preparation of formaldehyde gas sensor
[0058] (1) dissolving lanthanum nitrate, iron nitrate, samarium oxide, N,N-dimethylformamide and polyvinyl pyrrolidone in dilute nitric acid to obtain a mixed solution, then adding chloroauric acid to the mixed solution and stirring for 4 hours to obtain a precursor solution;
[0059] The added amounts of the lanthanum nitrate, ferric nitrate, samarium oxide, N,N-dimethylformamide, polyvinyl pyrrolidone, chloroauric acid and dilute nitric acid are 292.41 g: 241.85 g: 17.44 g: 50 mL: 50 g: 2.43 g: 180 mL.
[0060] (2) preparing a fiber intermediate from the precursor solution by electrospinning, wherein the electrostatic voltage range is 15 kV, and the distance between the needle of the syringe used for electrospinning and the collector aluminum foil is 20 cm;
[0061] The fiber intermediate is calcined at 800° C. for 2 hours to ensure that hydrocarbons in the fiber intermediate are completely burned out. After cooling to room temperature, the fiber intermediate is evenly ground for 5 hours to obtain a formaldehyde gas-sensitive material having a particle size of 60-100 nm.
[0062] (3) The formaldehyde gas-sensitive material, deionized water and pine oil were mixed in an amount ratio of 2 g: 6 mL: 2 mL to obtain a slurry, and the slurry was spin-coated on the surface of an aluminum oxide ceramic tube at a rotation speed of 600 rpm to make a coating thickness of 6 μm. The tube was aged in air at 240° C. for 16 h to obtain a formaldehyde gas-sensitive sensor.
[0063] Comparative Example 1:
[0064] The difference between this comparative example and Example 1 is that in step (1), samarium oxide and chloroauric acid are not added, that is, the obtained formaldehyde gas-sensitive material is LaFeO3 (lanthanum ferrite).
[0065] Comparative Example 2:
[0066] The difference between this comparative example and Example 1 is that in step (1), samarium oxide is not added and the amount of chloroauric acid added is adjusted, that is, the prepared formaldehyde gas-sensitive material is 1 wt% Au-LaFeO3.
[0067] Comparative Example 3:
[0068] The difference between this comparative example and Example 1 is that in step (1), no chloroauric acid is added, that is, the prepared formaldehyde gas-sensitive material is La 0.9 Sm 0.1 FeO3.
[0069] Comparative Example 4: 2wt% Au-La 0.9 Sm 0.1 FeO3
[0070] The difference between this comparative example and Example 1 is that in step (1), the added amounts of lanthanum ferrite, ferric nitrate, samarium oxide, N,N-dimethylformamide, polyvinyl pyrrolidone, chloroauric acid and dilute nitric acid are 292.41 g: 241.85 g: 17.44 g: 30 mL: 30 g: 4.86 g: 100 mL; that is, the doping amount of Au in the obtained formaldehyde gas-sensitive material is greater than 1%.
[0071] Comparative Example 5: 0.5wt% Au-La 0.9 Sm 0.1 FeO3
[0072] The difference between this comparative example and Example 1 is that in step (1), the added amounts of lanthanum ferrite, ferric nitrate, samarium oxide, N,N-dimethylformamide, polyvinylpyrrolidone, chloroauric acid and dilute nitric acid are 292.41 g: 241.85 g: 17.44 g: 30 mL: 30 g: 1.215 g: 100 mL; that is, the doping amount of Au in the obtained formaldehyde gas-sensitive material is less than 1%.
[0073] Test Example 1: Structural Characterization
[0074] Figure 1 The XRD patterns of the formaldehyde gas-sensitive materials obtained in Example 1 and Comparative Examples 1-5 are as follows: Figure 1 It can be seen that the crystallization peaks correspond to the (121), (202) and (240) phases of LaFeO3 (No. 37-1493). Figure 2 The SEM image of the formaldehyde gas-sensitive material obtained in Example 1 at a magnification of 1 μm is shown in FIG. Figure 2 It can be seen that the prepared gas-sensitive material presents a typical hollow nanotube micromorphology, the specific surface area and porosity of the material are increased, and the reaction sites and transmission channels of gas molecules are increased. Figure 3 The EDS graphs of the formaldehyde gas-sensitive materials prepared in Example 1 and Comparative Examples 1-5 are shown in FIG. Figure 3 It can be seen that Au and Sm elements exist in the formaldehyde gas-sensitive material prepared in the embodiment.
[0075] Test Example 2: Gas Sensing Performance Test
[0076] The formaldehyde gas-sensitive materials prepared in Example 1 and Comparative Examples 1-5 were coated on the sensing film to detect the gas-sensitive response (Rg / Ra), where Ra is the resistance of the sensor in the air and Rg is the resistance of the gas being measured. The experimental environment was: RH 20% and ambient temperature 20°C.
[0077] Figure 4The relationship between the response of the formaldehyde gas-sensitive materials prepared in Comparative Examples 1-5 and Example 1 to 1 ppm formaldehyde gas and temperature is shown in FIG. Figure 4 It can be seen that the optimal working temperature of formaldehyde gas-sensitive material is 120°C; the response of LaFeO3 material modified with Au element to formaldehyde is greater than that of pure LaFeO3 material not modified with Au element, and after doping with Sm element, the performance of the material is further improved.
[0078] Figure 5 The graph is a graph showing the relationship between the gas-sensing performance of the formaldehyde gas-sensitive materials prepared in Comparative Examples 1-5 and Example 1 and the formaldehyde gas concentration. Figure 5 It can be seen that with the increase of gas concentration, the gas sensing performance of the formaldehyde gas-sensitive material increases accordingly, but when the gas concentration exceeds 5ppm, the increasing trend of the gas sensing performance slows down; at any concentration, the 1wt% Au-La prepared in Example 1 0.9 Sm 0.1 FeO3 perovskite materials respond more to formaldehyde than other perovskite materials.
[0079] Figure 6 The following is a schematic diagram of the response of the formaldehyde gas-sensitive materials prepared in Comparative Examples 1-5 and Example 1 to various gases at 1 ppm. Figure 6 It can be seen that when exposed to various gases, the 1wt% Au-La prepared in Example 1 0.9 Sm 0.1 The selectivity of FeO3 to formaldehyde gas is higher than that of the formaldehyde gas-sensitive materials prepared in Comparative Examples 1-5.
[0080] Figure 7 This is a dynamic schematic diagram showing the response of the formaldehyde gas-sensitive materials prepared in Examples 1-5 and Example 1 to formaldehyde gas of different concentrations over time under the same working temperature and humidity environment. Figure 7 It can be seen that the 1wt% Au-La prepared in Example 1 0.9 Sm 0.1 FeO3 formaldehyde gas-sensitive material can detect extremely low concentration (0.1ppm) of formaldehyde gas and has obvious response characteristics.
[0081] Figure 8 The graph is a relationship between the response of the formaldehyde gas-sensitive materials prepared in Examples 1-5 and Example 1 to 1 ppm formaldehyde gas and the relative humidity of the environment. Figure 8 It can be seen that 1wt% Au-La 0.9 Sm 0.1When the relative humidity of FeO3 is below 60%, the response to formaldehyde gas changes very little, and the change rate is within 5%. For pure LaFeO3 formaldehyde gas-sensitive material, it shows a significant downward trend after the relative humidity exceeds 40%. Surface Au element modification and Sm element doping can improve the relative humidity adaptability of LaFeO3 perovskite materials. In the actual use of sensors, most of the environmental humidity is below 60%, indicating that the effect of humidity on 1wt% Au-La can be ignored in the actual detection process. 0.9 Sm 0.1 Effect of formaldehyde gas response on FeO3 perovskite materials.
[0082] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a formaldehyde gas-sensitive material, characterized in that: The following steps are involved: (1) Lanthanum nitrate, iron nitrate, samarium oxide, N,N-dimethylformamide and polyvinyl pyrrolidone are mixed and dissolved in dilute nitric acid to obtain a mixed solution, and chloroauric acid is added to the mixed solution and stirred to obtain a precursor solution; (2) preparing a fiber intermediate from the precursor solution by an electrostatic spinning method, calcining the fiber intermediate and grinding it to obtain a formaldehyde gas-sensitive material; The prepared formaldehyde gas-sensitive material is Xwt% Au-La y Sm 1-y FeO3, Xwt% is the doping amount of Au in the formaldehyde gas sensitive material, 0.5wt%≤Xwt%≤3wt%, 0<y≤0.
3.
2. The method for preparing the formaldehyde gas-sensitive material according to claim 1, characterized in that: In step (1), the added amount ratio of the lanthanum nitrate, ferric nitrate, samarium oxide, N,N-dimethylformamide, polyvinyl pyrrolidone, chloroauric acid and dilute nitric acid is (0.5-3) mol: (0.5-3) mol: (0.01-0.2) mol: (30-60) mL: (20-50) g: (1-20) g: (100-200) mL.
3. The method for preparing the formaldehyde gas-sensitive material according to claim 1, characterized in that: In step (2), during the electrospinning process, the electrostatic voltage range is 10 kV-20 kV, and the distance between the needle of the syringe used for electrospinning and the collector is 10 cm-20 cm.
4. The method for preparing the formaldehyde gas-sensitive material according to claim 1, characterized in that: In step (2), the calcination temperature is 600-800°C, the calcination time is 2-5h, and the injection rate is 0.5mL / h-0.8mL / h.
5. A method for preparing a formaldehyde gas sensor, characterized in that: The following steps are involved: The formaldehyde gas-sensitive material, deionized water and pine alcohol are mixed to obtain a slurry; the slurry is spin-coated on the surface of an aluminum oxide ceramic tube and aged to obtain a formaldehyde gas-sensitive sensor; The formaldehyde gas-sensitive material is Xwt% Au-La y Sm 1-y FeO3, Xwt% is the doping amount of Au in the formaldehyde gas sensitive material, 0.5wt%≤Xwt%≤3wt%, 0<y≤0.
3.
6. The method for preparing the formaldehyde gas sensor according to claim 5, characterized in that: The aging temperature is 180-240℃, and the aging time is 16-24h.
7. The method for preparing the formaldehyde gas sensor according to claim 5, characterized in that: The addition ratio of formaldehyde gas-sensitive material, deionized water and pinene alcohol is (1-3) g:(3-9) mL:(1-3) mL.
Citation Information
Patent Citations
NASICON based hybrid potentiometric type SO2 sensor using LaxSm1-xFeO3 as sensitive electrode material and preparation method thereof
CN107091868A
Gas sensitive material, gas sensor, and preparation method and application thereof
CN117169292A
Gas sensor operation with feedback control
WO2009024774A1